El problema de la violencia juvenil: análisis teorético y de programas de intervención conductual - Montgomery Urday, William (1998)
In this article it's saying that treatment of youth violence in our context is, generally, of diagnosis kind, except some applications in minor scale. But now we have a behavioural technology developed for this in other countries, with exitous proofs adapted and maked to our reality. The functional analysis implicated in this technology is embracing they antecedent, present and consequent dimensions of aggressive episode, for identification of risk factors and postulating the corrective actions. I suggest that behavioural programs are systematic interventions and they have solid empirical dales. They are powerful alternatives for integrating commentary strategies in conjunction with experts.